2019
DOI: 10.35812/cellulosechemtechnol.2019.53.59
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Suitability of Pressmud and Coir Pith for Use as Soilless Substrate by Sem, Xrf, Uv-Vis and Ftir Spectroscopy Techniques

Abstract: Pressmud and coir pith are bulk organic substrates useful for constituting soilless media. In the instrumental investigation, the lignocellulosic organic substances predominant in coir pith and pressmud were characterized in terms of proximate constituents, elemental composition and functional groups. The elemental composition studies by X-ray fluorescence spectroscopy (XRF) and proximate constituent analysis showed that both coir pith and pressmud contain sufficient amounts of macro-and micro-nutrients, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The peak at around 549.29 cm −1 is due to Si-H bond stretching [42]. Likewise, Rout et al [43] investigated a similar pattern when they analyzed the press mud using FTIR spectroscopy. The data in the present study showed that treatment with press mud and Trichoderma caused a significant boost on morphological criteria and yield as compared to plants inoculated with nematodes.…”
Section: Discussionmentioning
confidence: 89%
“…The peak at around 549.29 cm −1 is due to Si-H bond stretching [42]. Likewise, Rout et al [43] investigated a similar pattern when they analyzed the press mud using FTIR spectroscopy. The data in the present study showed that treatment with press mud and Trichoderma caused a significant boost on morphological criteria and yield as compared to plants inoculated with nematodes.…”
Section: Discussionmentioning
confidence: 89%
“…Firstly, PM provided P along with other nutrients to growing plants (Table 1). Secondly, PM addition added carbon to soil which subsequently increased soil microbial multiplication (Rout & Arulmozhiselvan, 2019). This increase in microbial proliferation might had supported more plant growth promotion activities in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The ash content in PM is also significant. The ash content is on an average at least 20% except in the work reported by Rout and Arulmozhiselvan [25]. PM, in combination with bagasse, is also sometimes used as fuel [20].…”
Section: Characterization Of Sugarcane Pmmentioning
confidence: 99%